Impact of social media usage on sustainable performance of SMEs: The role of digital leadership, innovation capabilities and organizational commitment - Yasin Awwab; Avanti Fontana (President University, 2022)
The development of the world of technology has made the increasing use of social media in carrying out the operational role of small and medium-sized businesses (SMEs) as well as has triggered a major transformation in the role of corporate social technology in SMEs. Social media is often used in companies for work and non-work purposes, which is then influenced by the existing digital leadership. Existing research on the use of social media, innovation capabilities, organizational commitment and performance generated by SMEs, and the role of digital leadership is quite sparse, especially in research in developing countries. This study explores the relationship between the use of social media and the role of digital leadership on innovation capabilities and organizational commitment to improving the sustainable performance of SMEs. To do this, a total of 127 samples of survey results were obtained from managers who manage SMEs in Indonesia. This study uses Partial least squares structural equation modeling (PLS-SEM), with results showing that the use of social media moderated by digital leadership can increase innovation which then affects the sustainable performance of SMEs. This study outlines the theoretical contributions and practical implications.